(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Grid computing has been a buzzword in information technology since past few years. Grid computing is an infrastructure involving collaboration of computers, databases network resources available, to perform manipulation of intensive and large scale data set problems. The hike in the complexities of computational problems in modern era of science and technology forced the engineers and scientists to cross the organizational boundaries to get desired data manipulation. The best logical solution to this issue is distribution of the problem set over multiple computational resourcesnodes. Several solutions to grid computing has been developed and are still evolving, since the notion of Grid sprang up in mid 1990s, most of which came from the academic research projects. This paper presents an introduction to Grid computing providing insight into the essential features, architecture, scope and challenges of grid computing.